Using Smart City Technology to Make Healthcare Smarter - Cook, Diane J.; Duncan, Glen; Sprint, Gina; Fritz, Roschelle L. (Proceedings of the IEEE, 2018)
Smart cities use information and communication technologies (ICTs) to scale services include utilities and transportation to a growing population. In this paper, we discuss how smart city ICTs can also improve healthcare effectiveness and lower healthcare cost for smart city residents. We survey current literature and introduce original research to offer an overview of how smart city infrastructure supports strategic healthcare using both mobile and ambient sensors combined with machine learning. Finally, we consider challenges that will be faced as healthcare providers make use of these opportunities.